Legal Prospects of Temporary Protection for Citizens of Ukraine in the Member States of the European Union - Kozhura, Liudmyla; Zadereiko, Svitlana; Ryzhuk, Yuliia; Vlasenko, Valentyna; Zamryha, Artur (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The article examines the legal prospects of the international mechanism of temporary protection for citizens of Ukraine in the member states of the EU. The issue of temporary protection is regulated by Directive 2001/55/EC dated July 20, 2001, which was activated for the first time in history by EU Council Decision 2022/382 dated March 4, 2022, which provides immediate protection and access to rights in the EU, including the right to residence, access to housing, access to the labour market, access to education for children, the right to medical and social assistance. The Directive 2001/55/EC was activated for the first time in history for Ukrainians who were fleeing war masse after the full-scale invasion of the Russian army in Ukraine, and the 3-year period is the maximum for its effect. However, the war in Ukraine continues, and the EU Council decided to extend temporary protection for Ukrainian citizens in the member states of the European Union until March 4, 2026. Experts' predictions regarding when the war in Ukraine will end vary greatly (from this year to decades). Therefore, the issue of the legal status of Ukrainian citizens in the member states of the European Union becomes relevant, and options for a solution need to be found. However, temporary legal status for an indefinite period is not the best solution; citizens of Ukraine found themselves in EU member states in waiting mode without a time frame. This does not contribute to the full integration of Ukrainians into European society or to their decision to return to Ukraine. The article aims to analyse possible legal options for solving this issue based on the complex use of such methods of scientific knowledge as historical, formal-legal, comparative-legal and prognostic. It was concluded that in modern political conditions, it is necessary to look for a permanent legal mechanism for the stay of citizens of Ukraine in the EU member states rather than a temporary one.